Empowering Adolescent Peer Cadres for Tuberculosis Prevention: The “PEKA TB” Initiative at SMPN 31 Padang - Masrizal; Widoyo, Ratno; Perwati, Ane Dayu; Fauzi, Falah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2025)
Tuberculosis (TB) remains a major public health issue, particularly among adolescents in densely populated school environments with poor ventilation. This community service aimed to strengthen TB prevention and control efforts through the establishment and empowerment of “PEKA TB” (Pencegahan dan Penanggulangan Tuberkulosis) cadres at SMPN 31 Padang. The activity employed a pre–post test design with an educational and participatory approach, involving 34 students from grades VIII and IX as peer health cadres. The intervention consisted of interactive lectures, discussions, and simulations on TB transmission, prevention, and the PEKA TB framework (Examine–Educate–Coordinate–Act). Evaluation using structured questionnaires measured knowledge, attitude, and practice before and after the intervention. The results showed significant improvements across all variables, indicating that peer-based education effectively enhanced students’ awareness, attitudes, and preventive behaviors toward TB. The empowerment of adolescent cadres successfully fostered active participation in school health promotion and strengthened collaboration between schools and local health authorities. This initiative demonstrates that student-centered, peer-led education is a sustainable strategy to create a healthy, TB-free school environment.